Corrective Proximal Humerus Osteotomy with Blade Plate Osteosynthesis in Adolescents: A Report of 2 Cases. Issue 3 (July 2021) - Fabricant, Peter D.; Anatone, Alex J.; Lin, Kenneth M.; Brusalis, Christopher M.; Mackie, Alexandra T.; Pinnamaneni, Sridhar; Taylor, Samuel A.
Abstract : Case: Two cases are presented to highlight the indications, surgical technique, and early clinical outcomes associated with proximal humerus corrective osteotomy using a 90° cannulated blade plate in adolescent patients. Conclusion: A complex deformity of the proximal humerus in the adolescent patient poses an uncommon yet debilitating clinical condition that is challenging to manage. We report a unique method for surgical correction and fixation using an infant hip osteotomy 90° blade plate that restores native shoulder anatomy, improves function, and has led to early clinical success.